Utility Pricing and the Poor : Lessons from Armenia - Lampietti, Julian A.; Kolb, Anthony A.; Gulyani, Sumila; Avenesyan, Vahram (Washington, DC: World Bank, 2013)
Increasing cost recovery for utilities is a cornerstone of the Government of Armenia's economic reform program. This report assesses the 1999 electricity tariff increase and the potential for future improved water sector cost recovery, with particular attention to questions of service accessibility and affordability for the poor . The burden of energy expenditures is large for most households, particularly for the poor. Electricity makes up the bulk of these expenditures, and a further increase in tariffs, without increasing access to low cost substitutes, would lead to the greatest hardship for the urban poor. Future electricity tariff increases should be closely coordinated with improved price response prediction and credible action to mitigate the potential impact on the poor and the environment. The water utilities are caught in a low-level equilibrium trap, characterized by decreasing service quality and revenue. The water utilities must break out of this trap by generating more revenues through improved service delivery. A two-stage approach is recommended. In the first stage, revenues should be increased by enforcing payment from the households that currently have reliable service but are not paying their bills, in the second stage, after collection capacity is strengthened, the utility should start a program of tariff adjustments, based on improved service and meter-based billing.